Patient satisfaction after unilateral oncoplastic volume displacement surgery for breast cancer, evaluated with the BREAST-Q™ - Gardfjell, Anna (World J Surg Oncol, 2019)
BACKGROUND: Oncoplastic breast-conserving surgery allows larger resections in unfavorable locations, with an improved chance of preserving esthetics. Indications and timing for potential contralateral surgery to obtain symmetry are not clear. The aim of this study was to evaluate patient satisfaction after unilateral oncoplastic volume displacement surgery, to investigate potential risk factors for lower patient satisfaction and to assess patient wish for contralateral surgery. METHOD: A cohort of 144 women, consecutively treated for breast cancer with unilateral breast-conserving oncoplastic volume displacement surgery, followed by radiotherapy and with an unoperated contralateral breast, was sent the BREAST-Q™ breast-conserving therapy (BCT) and a study-specific questionnaire. In all, 120 women (83%) responded. For these women, the median value for resected specimen weight was 92 g (range 14–345) and for the estimated percentage of the breast volume excised 15% (range 3–35%). RESULTS: The median patient-reported score for “Satisfaction with breast” (BREAST-Q™ BCT) was 74/100. Factors associated with a score below median value in a simple logistic regression model adjusted for age and BMI were axillary clearance (OR 2.46, 95% CI 1.09–5.56), neoadjuvant chemotherapy (OR 3.26, 95% CI 1.15–9.24), and low breast density (OR 2.32 95% CI 1.02–5.29). Thirteen women (11%) were interested in contralateral surgery. CONCLUSION: Most patients in this study cohort, who had undergone breast-conserving therapy with oncoplastic volume displacement techniques, were satisfied with their breasts without surgery to the contralateral breast. This indicates that contralateral surgery to achieve symmetry only should be performed after individual evaluation and as a delayed procedure.